1991
DOI: 10.1152/jappl.1991.71.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invariant sympathetic activity on cutaneous circulatory responses to heat stress

Abstract: This study investigated the role of sympathetic withdrawal on blood flow responses in cutaneous arteriovenous anastomoses (AVAs) and capillaries to direct and indirect heat stress. This was achieved by clamping sympathetic activity (SC) to the tail of anesthetized rats so that constrictor tone remained invariant during exposure of either the animal's tail (direct heating) or body (indirect heating) to a 35 degrees C environment. Flow through the AVAs in the tail was evaluated by laser-Doppler flowmetry (LDF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…For example, Young et al 5 reported that the blood vessels in the tail of conscious female rats dilate when ambient temperature is higher than 29°C. But because their rats were confined in a small cage, augmented sympathetic nerve activity due to stress would have suppressed vasodilation 6 . Although differences in motor activities between different stages in the estrous cycle have been thought to be the reason for the differences in body temperature in female rats, 1 the high‐estrogen rats in the present study did not evidently move more than the low‐estrogen rats.…”
Section: Average and Standard Deviation Of Core Temperature (Tc) Taimentioning
confidence: 53%
“…For example, Young et al 5 reported that the blood vessels in the tail of conscious female rats dilate when ambient temperature is higher than 29°C. But because their rats were confined in a small cage, augmented sympathetic nerve activity due to stress would have suppressed vasodilation 6 . Although differences in motor activities between different stages in the estrous cycle have been thought to be the reason for the differences in body temperature in female rats, 1 the high‐estrogen rats in the present study did not evidently move more than the low‐estrogen rats.…”
Section: Average and Standard Deviation Of Core Temperature (Tc) Taimentioning
confidence: 53%
“…Young and Dawson (33) reported that rats could dissipate ϳ25% of basal metabolic heat production through the tail by changing tail blood flow. In addition, tail blood flow is controlled by sympathetic nerve activity (14,19). It is known that fasting modulates sympathetic nerve activity in some organs such as the liver, adrenal gland, and adipose tissue (2,23,(34)(35)(36).…”
mentioning
confidence: 99%
“…Microcirculatory blood flow measurements were made within the subepidermal vascular plexus of the rat's tail in accordance to previous methods (24,25,26,27,34). The vessels investigated in this study are referred to as capillaries, because their luminal diameters (from 3.5 to 4) are of capillary dimension.…”
Section: Measurementsmentioning
confidence: 99%
“…The vessels investigated in this study are referred to as capillaries, because their luminal diameters (from 3.5 to 4) are of capillary dimension. Measurements of blood cell velocity (BCV) were obtained in individual vessels within the subepidermal vascular plexus by a videodensitometry method that was a computerized version of an analog system previously used (25,26,27,34) and described (25).…”
Section: Measurementsmentioning
confidence: 99%